Transforming From Conventional Teaching Environment to LearnerCentred Teaching Environment With the use of Interactive Multimedia Module in Tertiary Education - Yap, Wei Li; Neo, Mai; Neo, Tse Kian (2016)
It has been many centuries conventional teaching is in practice but its limitations are noted. Some slow learners might have difficulty to follow and some fast learners might find it boring listening to the repeating explanations. At many times lecturers find it not enough time for discussion or questions and answers questions. Some students are not ready to ask questions at the end of the class too. Due to this, many universities have taken action to encourage lecturers to move to a more learner-centred teaching environment where it allows two ways communication between lecturers and students and then enhances learner understanding and motivation. However, the transition has been slow because lecturers find it risky and lack of confidence in moving away from conventional teaching approach as they themselves were taught in such environment. Weimer’s Learner-Centred Teaching Model could serve as a guidance to help lecturers in planning and implementing a more interesting teaching environment which puts the learning responsibility onto students. The use of technology in classroom is common nowadays as our students are tech savvy and they would find it interesting to enjoy the benefits of technology in learning process. Hence, a different learning environment which incorporates technology would motivate and engage students more. In this research, a multimedia-mediated learning module is included in the implementation of this learner-centred teaching environment. In order to show how one can gradually transform from the conventional teaching environment to learner-centred teaching environment, this research proposes a framework which explains different outcomes obtained from three different learning environments. The results obtained from the research were triangulated based on the pre/post-tests, survey and written comments to present the implications from the implementation of different learning environments.